DEVELOPMENT OF LOOPER MECHANISMS FOR SEWING MACHINES WITH A P-SHAPED PLATFORM AND THEIR KINEMATIC SYNTHESIS - MACHULSKYI, VALERII; HOROBETS, VASYL; ZLOTENKO , BORYS (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The aim of the study was to develop new structures and designs of looper mechanisms with improved dynamic and functional characteristics compared to existing corresponding mechanisms and to determine their parameters using specific equipment units as examples. The objects of the research were the new structures of looper mechanisms proposed by the authors. To determine their parameters, a kinematic synthesis methodology developed by the Department of Mechanical Engineering at Kyiv National University of Technologies and Design was applied. This methodology takes into account not only geometric and kinematic characteristics but also functional aspects as input data.The study also utilized well-known methods of mechanism and machine theory for kinematic analysis and synthesis of lever mechanisms. The developed looper mechanisms offer significant advantages in terms of dynamics and functionality compared to existing analogs due to their simpler structure and reduced number of links. These advantages make the implementation of the proposed mechanisms in production promising, both for modernizing or repairing existing equipment and for designing new machines.The authors developed the structure and design of four new looper mechanisms for typical sewing machines with a P-shaped platform. These mechanisms achieve structural simplification and improved dynamic characteristics by using a simple kinematic scheme instead of a branched one, reducing the number of links, and expanding technological capabilities through additional parameter adjustment compared to similar mechanisms in existing sewing machines.Furthermore, as an example, the parameters of the new mechanisms were determined using the mentioned synthesis methodology, specifically for typical sewing machines with a P-shaped platform. Additionally, the design of these mechanisms was developed using the SolidWorks computer-aided design system, which facilitates their implementation in production.
Keywords: Structure of lever mechanisms; kinematic chain; kinematic link; synthesis parameters; mechanism design; sewing machine